(untitled) (Computer systems and information technologies, 2022)
The presented paper sets the goal of providing computer engineering courses based on a single-board computers (SBC) with the organization of the remote education process. The devised approach relies on the connection to the local area network (wired or wireless) of the university, making the board accessible to the internal users, and creation of a network tunnel between the remote user and connected parts. These actions are accompanied by assignments of necessary permissions to the users of the system. First, the requirements of each involved actor were considered and as a result of that further understanding of the network communication process, network management and administration, software requirements, etc. was acquired. According to these results, analysis of the capabilities of SBC in terms of its connectivity was performed and, finally, the architecture was realized on the available hardware with regard to the peculiarities of the specific subject. The article establishes all the necessary details on the implementation of the proposed architecture and discusses results of the testing performed as a part of the specific course. During the testing stage, the deployed system based on FriendlyARM Nano Pi allowed us to organize the course on Real-Time Embedded Computer Systems and successfully finish all related activities under circumstances of remote education. It was demonstrated that the proposed organization is reliable as demonstrates conceivable performance even under condition of multiple simultaneous connections to the target board. From the administrative point of view, the solution is highly configurable which is a huge advantage for the lecturer and for the administrator. The devised architecture has a potential in terms of improvement and scalability because it consumes relatively low network capacity and is easy to deploy under any circumstances.